Contribution of Sweet Orange Farming Income to Family Income in OKU Regency - Sherli Yuniar; Yetty Oktarina (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Oranges are fruits originating from small tree species or shrubs in the Genus Citrus of the Rue family. Oranges are fruit commodities that are quite profitable to cultivate. This research was conducted in OKU Regency. The results showed that the contribution of sweet orange farming was 96.23 percent of the total family income, which is categorized as large and serves as the primary source of household income for farmers in OKU Regency